From Seascapes of Extinction to Seascapes of Confidence - Territorial Use Rights in Fisheries in Chile: El Quisco and Puerto Oscuro - Gloria L. Gallardo Fernández (Co-Action Publishing, 2021)
An important contribution to our understanding of the multifaceted challenges underlying sustainable solutions to ecological fisheries, the book describes how, in Chile, indiscriminate harvest of the edible shellfish Concholepas concholepas (false abalone or Loco), has been threatening not only the living of small-scale artisan fishers but also the ecosystem. In an attempt to strengthen the fishers’ livelihoods and at the same time recuperate the fish, the Chilean government introduced the regulatory measure: Management and Exploitation Areas for Benthic Resources (MEABRs), locally known as Management Areas (MAs) and internationally as Territorial Use Rights in Fisheries (TURFs). The author uses a participatory approach to this interdisciplinary issue, examining how the MAs have impacted on two fishing organizations and localities that depend for their survival on benthic resources: El Quisco (Valparaíso Region) and Puerto Oscuro (Coquimbo Region). Placed in the larger context of the critical situation of fisheries in the world, the book not only offers an example to other communities but also an insight into the complex ways politics links to economics, the local links to the regional and the global, and nature to society. Español: Una importante contribución para nuestra comprensión de los desafíos multifacéticos que subyacen bajo soluciones sustentables para una pesca ecológica es este libro que describe como en Chile, la extracción indiscriminada de la especie comestible Concholepas concholepas (abulón falso o Loco) llegó a amenazar no tan sólo la sobrevivencia de los pequeños pescadores artesanales, sino también el ecosistema. En un esfuerzo por fortalecer el sustento de los pescadores y al mismo tiempo por recuperar la especie, el gobierno chileno introdujo la medida regulatoria Áreas de Manejo y Explotación de Recursos Bentónicos (AMERBs), conocida localmente como Áreas de Manejo (AMs), e internacionalmente como Derechos Territoriales de Pesca (TURFs). La autora usa un enfoque participativo para este tema interdisciplinario, examinando como las AM han impactado en dos organizaciones y localidades pesqueras que dependen para su sobrevivencia de los recursos bentónicos como son El Quisco (Región de Valparaíso) y Puerto Oscuro (Región de Coquimbo). Puesto en un contexto mayor de la crítica situación de las pesquerías en el mundo, el libro no es solo un ejemplo para otras comunidades sino que ofrece también una mirada sobre las complejas maneras en las cuales la política se entrelaza con la economía, lo local con lo regional y global, y la naturaleza con la sociedad.